PENGARUH PELARUT PARTISI PADA KANDUNGAN FENOLAT TOTAL DAN AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BATANG TOONA SINENSIS - Murningsih, Tri (BERITA BIOLOGI, 2015)
Toona sinensisis a plant species included in Meliaceae family.In China, the leaves of T. sinensis are used in Chinese traditional and herbal drugs for the treatment of rheumatoid arthritis, urethritis,gastric ulcer, enteritis, diarrhea, chronic dysentery,itching, andcancer. Barkis the part of plant that contains phenolic compounds. Phenolic compounds have redox properties that can act as a reducing agent or hydrogen donor so its have antioxidant properties. In this study, four types of solvent were used for partition of T. sinensis bark extract.The fractions were used to examine the effects of solvents on total phenolic content sand antioxidant activity. Total phenolic content of fractions was determined using Folin-ciocalteu reagent while antioxidant activity was carried out using phosphomolybdenum, 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging, ferric reducing power and ß-carotene bleaching assay. Results showed that ethyl acetate fraction has the highest content of total phenolic compound (36,42 ± 0,05 mg GAE/g) and the stronggest of antioxidant activity on total antioxidant (34,44 ± 0,03mg AAE/g), DPPH radical scavenging (IC50= 35,23 µg/mL), ferric reducing power (IC50=128,55 µg/mL) and ß-carotene bleaching assay (IC50 fraksi (125,62 µg/mL). Instead of n-hexane fraction has the lowest content of total phenolic compound and the weakest of antioxidant activity of all antioxidant activity assay. It can be concluded that the difference in the polarity of the solvent partitioning lead to differences in total phenolic content and antioxidant activity.